Identification of the Effect of Water Stress on Yield Production and Evaluation of the Nutrient Content of Garut Tubers and Flour - Muhammad Khalimi; Rina Rismaya; Sutrisno Sutrisno (Journal of Global Sustainable Agriculture, 2023)
Arrowroot tubers (Maranta Arundinace L.) are a tuber plant that has potential as a source of carbohydrates. Arrowroot tuber plants have the potential to adapt well to various environmental conditions including water stress. The aim of this research was to identify the effect of water stress on yield production (number, weight, length and diameter) and evaluate the nutritional content of arrowroot tubers. This research used a Completely Randomized Design (CRD) with 7 water stress treatments, namely (P1) 15 days of waterlogging, (P2) 10 days of waterlogging, (P3) 5 days of waterlogging, (P4) daily watering, (P5) watering every 5 days, (P6) watering every 10 days, and (P7) watering every 15 days which was repeated in 2 experimental repetitions and 2 measurement repetitions. The results of the research showed that there was no decrease in yield in treatments P1 to P3, however in treatments P6 and P7 there was a difference in the yield of lower tuber weight compared to the daily watering treatment (P4) and the once every 5 days watering treatment (P5). Treatment The results of proximate analysis of arrowroot tubers with the best yield production (P5) showed that the water, ash, fat, protein and carbohydrate content of fresh tubers were respectively 69.82%, 1.47%, 0.21%, 0, 45% and 28.15%, while arrowroot flour is 2.28%, 4.77%, 0.33%, 1.47% and 91.16%. The results of this research provide information that arrowroot plants can be planted on land that has the potential to be flooded during the arrowroot growing season, but arrowroot plants require sufficient water to optimize their production. The high carbohydrate content of arrowroot tubers reflects its potential as an alternative food source to replace wheat and rice.